Superbacteria carry new gene that makes them resist all antibacterials - Marchese Morales, Adolfo (2016)
A group of Chinese scientists have found a new gene in gram negative bacteria, the MCR-1. This gene has given pathogenic bacteria resistance to colistin, which is the antibacterial that medical doctors use as last line of defense against multi-drug resistant infections. Superbacteria with MCR-1 will be potentially epidemic, and diseases that were believed to be controlled such as pneumonia, tuberculosis and urinary tract infections could be lethal again.